The Effect of Principal’s Participatory Leadership and School’s Culture on the Implementation of Total Quality Management - Rahayu, Yuni; Ahyani, Nur; Effendi, Darwin (Journal of Social Work and Science Education, 2023)
This study aims to determine whether there is influence between the Principal’s Participatory Leadership and School’s culture on the Implementation of Total Quality Management (TQM) at SMK Negeri 1 Prabumulih. The population of this study were 100 teachers at Prabumulih State Vocational School 1 and the sample taken using the Slovin formula was 80 teachers. This research uses quantitative with correlation and descriptive methods, while the sampling is done by random sampling, the research instrument uses a questionnaire that has been tested for validity and reliability. The results of the research hypothesis using the regression test, namely simple linear regression and multiple linear regression using SPSS indicate that there is a significant influence between the Principal’s Participatory Leadership and School’s culture on the Implementation of TQM at SMK Negeri 1 Prabumulih. Then between the Participatory Leadership of the Principal and the School’s culture on the Implementation of TQM at SMK Negeri 1 Prabumulih is equal, so the alternative hypothesis is accepted which means that there is a significant influence simultaneously between the Principal’s Participatory Leadership and School’s culture toward the Implementation of TQM.